2022
DOI: 10.4103/jomfp.jomfp_446_20
|View full text |Cite
|
Sign up to set email alerts
|

A case of migratory stomatitis in a young male patient

Abstract: Migratory stomatitis (MS) is an uncommon inflammatory condition with unclarified etiology, which despite its benign nature, may raise concerns for patients and diagnostic difficulties for professionals. This case report aims to describe the clinical features of a patient who presented with MS in conjunction with benign migratory glossitis (BMG), and its diagnostic process and management. The patient, a 25-year-old man, sought diagnosis of an oral condition, with cyclic behavior, which had been causing him grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In this way, they may not be identified by patients or misdiagnosed by some professionals. 20 This article describes the case of a patient with geographic tongue and migratory stomatitis in the soft palate discovered in a routine examination.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, they may not be identified by patients or misdiagnosed by some professionals. 20 This article describes the case of a patient with geographic tongue and migratory stomatitis in the soft palate discovered in a routine examination.…”
Section: Discussionmentioning
confidence: 99%
“…GT most often affects the front two thirds of the tongue dorsum. Lesions tend to migrate and are often associated with fissured tongue 1 . GT is mostly asymptomatic, but patients sometimes report sensitivity to a certain type of food.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the tongue epithelium is continually renewed by proliferation, maturation, and apoptosis processes, which are partly controlled by the epidermal growth factor (EGF) [ 4 ]. Occasionally, lesions are found in other oral cavity places, called migratory stomatitis, geographic stomatitis, or ectopic GT [ 5 , 6 ]. Studies have shown a significant association between GT and fissured tongue (FT) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As main symptoms, pain, burning sensation, and discomfort are occasionally reported by some individuals [ 3 , 6 , 18 ] and can be treated with mouthwashes containing anesthetic, and/or antihistamines, and/or topical corticosteroids [ 3 ].…”
Section: Introductionmentioning
confidence: 99%